Shariah-Compliant Marketing in the Digital Landscape: Ethical Principles and Implications for Contemporary Business Practice - Muhammad Azharuddin; Nina Dwi Setyaningsih; Hanim Misbah (IQTISHODUNA: Jurnal Ekonomi Islam, 2025)
The rapid expansion of digital economies has intensified the need to align marketing innovations with Shariah ethical principles. This study systematically reviews and synthesizes scholarly developments on Shariah-compliant marketing within digital environments by integrating literature from Islamic finance, governance, digital technology, and Muslim consumer behaviour. Combining a systematic literature review with bibliometric analysis of 130 Scopus-indexed documents published between 2001 and 2025, the findings reveal four dominant thematic domains: the operationalisation of core Islamic ethical principles through blockchain, AI, fintech, and smart contracts; the increasing relevance of transmedia storytelling for culturally grounded value communication; the rise of maqasid al-shariah–oriented governance frameworks to strengthen consumer protection and disclosure; and the influence of religiosity and literacy on technology acceptance. Despite significant growth, the field remains fragmented, with limited theoretical convergence between institutional digital innovation and consumer-facing ethical practices. The study proposes a forward-looking research agenda emphasising hybrid human–AI compliance systems, narrative governance in digital persuasion, and longitudinal assessment of ethical performance. These directions contribute to strengthening integrity, accountability, and value authenticity in Shariah-compliant marketing across contemporary digital ecosystems.